Empowering people in the business frontline: The Ruggie's framework and the capability approach - César G. Canton (Management Revue, 2012)
This paper explains how the Ruggie's framework for corporate human rights performance may benefit from a relationship with the capability approach. The capability approach is found to fit nicely with both human rights and managerial perspectives. Among the many reciprocal contributions these perspectives can make to each other, this paper places a specific focus on how the capability approach can strenghten the case for the universality of human rights by means of Nussbaum's list of capabilities; as well as get the Ruggie's framework specified in business settings by accounting for different factors of variability and aspects of freedom. A manager-friendly 4-step flow chart of practical reasoning is suggested and tested on the issue of gender equality in the firm.
Keywords: F23; J8; J24; M14; M50; 650; Ruggie's framework; capability approach; corporate responsibility; practical reasoning; gender equality